Anti-Hysteria Kit launched - Laili, Zulkepeli (Penerbit UMP, 2015)
Putrajaya, April 30 - Universiti Malaysia Pahang (UMP) continues to give the support and space for its researchers to work on their scientific researches that will not only have high impact on the university but also findings that can benefit the society.